Drying time and mixture composition effect on biomass of pine cone and palm shell - Radyantho, K.D.; Rusdan, A.; Suanggana, D.; Haryono, H.D.; Kan, E.F. (Universitas Mataram, 2025)
According to the International Energy Agency (IEA), global energy demand is expected to rise by 45% by 2030, with around 80% still met by fossil fuels. This necessitates urgent development of alternative energy sources, such as biomass, which is renewable and can help reduce organic waste. This study examines the impact of varying drying times and mixture compositions of palm shells and pine fruits on the characteristics of briquettes. These materials were chosen due to their availability and potential to mitigate environmental impacts.The research investigates the moisture content, calorific value, and ash content of the briquettes. Results show all briquette compositions meet the Indonesian National Standard (SNI) No. 1683:2021 for moisture content, though only WP3 fails to meet standards. Ash content for all variations exceeded the SNI threshold (≥ 10%). However, all met the calorific value standard, with WP3 achieving the highest value (6643.18 cal/g). ANOVA analysis indicates both mixture composition and drying time significantly affect moisture and ash content, but only drying time significantly impacts calorific value